Study of Granular Soil Behavior under Different Drainage Conditions - Ina Asha Nurjanah; Rama Indera Kusuma; Enden Mina; Woelandari Fathonah; Prastika Wahid Santoso; Midia Rahma; Abdurohim Abdurohim (JURUSAN TEKNIK SIPIL, 2026)
Granular soils, such as sand and gravel, exhibit distinct mechanical behavior depending on drainage conditions during loading. This study aims to evaluate the influence of drained and undrained conditions on shear strength, deformation characteristics, and pore water pressure response of granular soils through a comprehensive literature review. The research is grounded in classical soil mechanics theories and recent studies, without conducting laboratory testing, and instead focuses on a comparative analysis of previous findings.The results indicate that under drained conditions, granular soils generally exhibit higher shear strength due to the absence of excess pore water pressure, allowing effective stress to govern soil behavior. Dense granular soils tend to exhibit dilative behavior, which contributes to increased strength and stability. In contrast, under undrained conditions, the inability of pore water to dissipate leads to the generation of excess pore water pressure, reducing effective stress and shear strength. This condition is particularly critical in loose saturated sands, where contractive behavior may trigger instability or liquefaction.Furthermore, this study contributes by providing a conceptual synthesis that integrates effective stress, pore water pressure, and deformation behavior into a unified framework for understanding granular soil response under different drainage conditionsmore reliable and safer geotechnical engineering practices.